Magnetic susceptibility mapping: applications for the Meguma Group, central Nova Scotia - King, M. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1997)
An extensive magnetic susceptibility mapping program was undertaken in conjunction with re-processing and enhancement of aeromagnetic data over the Meguma Group of Nova Scotia. The ground follow-up consisted of several thousand in situ magnetic susceptibility measurements collected in conjunction with a detailed geological mapping program designed to identify the sources of newly resolved aeromagnetic anomalies. Analysis of the susceptibility data and magnetic mineralogy identified a strong correlation between general magnetic character and stratigraphy. This correlation can be confidently demonstrated at the member level (e.g., Glen Brook unit), however, more detailed relationship, correspond to lithological variations within a particular unit. For example, slate packages within the Steves Road, unit have a mean susceptibility of 0.41(±0.09) x 10"3 SI compared to 0.11(^0.09) x 10'3 SI, for the predominant meta-sandstone strata. Other examples include various lithologies in the Goldenville Halifax Transition zone Upper Beds unit, which consists of silty slate (kave~0.S8 x 10"3 SI), Mn-rich silt beds (kave~1.02 x 10° SI), and tightly folded sulphide rich sand beds (k,ve=1.68 x 10*3 SI). In situ susceptibility data is also an indicator of sulphide content in the slates of the Halifax Formation including pyrrho-tite and to a lesser degree, pyrite. The susceptibility readings also appeared to indicate anisotropy of magnetic susceptibility (AMS) in the slates where pyrrhotite grains were oriented parallel to well developed cleavage. Within the Goldenville Formation, magnetic susceptibility measurements frequently provide the only indication of lithological variations and hence facilitate the mapping of the monotonous metasandstone packages. Marker horizons can also be traced in a similar fashion.